A systematic review of ultrasonography in osteoarthritis. Issue 5 (14th April 2009) - Keen, H I; Wakefield, R J; Conaghan, P G
Abstract : Background: Ultrasonography has been increasingly utilised to aid the understanding and management of rheumatic conditions. In recent years there has been a focus on the validity and utility of ultrasonography in demonstrating joint pathology, although this has largely focused on inflammatory arthritis. Aims: To undertake a systematic review of the published literature evaluating ultrasonography as an assessment tool in osteoarthritis. Methods: Medline and Pubmed were searched to identify original manuscripts, published before June 2008, utilising ultrasonography to assess the joints of cohorts of subjects with osteoarthritis. Data were extracted from manuscripts meeting the inclusion criteria, with a particular focus on the pathology imaged, the definitions used, scoring systems and their metric properties. Results: Forty-seven studies were identified that utilised ultrasonography to assess structural pathology in osteoarthritis. Doppler function was only assessed in 10 studies and contrast agents in one. There was heterogeneity with regard to the pathology examined, the definition of pathology, quantification and the reporting of these factors. There was also a lack of construct and criterion validity and data demonstrating reliability and sensitivity to change. Conclusions: Whereas there is increasing evidence of the validity of ultrasonography in detecting structural pathology in inflammatory arthritis, more work is required to develop standardised definitions of pathology and to demonstrate the validity of ultrasonography in osteoarthritis.